Experienced and anticipated changes in household economic situation and childless women's short-term intentions to become mothers. Issue 2 (15th March 2019) - Kurowska, Anna
ABSTRACT: Despite the considerable volume of literature on the impact of economic conditions on childbearing, most studies have focused on the deterioration of the individual's economic situation and economic uncertainty. This study complements previous studies by exploring how both negative and positive changes to the household's economic situation impact the short-term intentions of childless women to become mothers. Furthermore, this study differentiates between past experiences of change and anticipated changes in the future. Multinomial logistic regressions are applied for childless women using pooled data from nine European countries. The results show that regardless of the changes to the household's economic situation in the five years preceding the survey, the anticipated improvement in its economic situation over the following five years decreased the chances of childless women experiencing childbearing uncertainty or negative short-term fertility intentions.